A Scoping Review on Repair Services Literature - Shawon, Niaz (My University, 2026)
The study systematically maps the body of knowledge on repair services to identify key themes, research gaps, and emerging trends. The scoping review analyzed 61 peer-reviewed articles (1983-2026) curated from an initial pool of 8359 documents indexed in Web of Science and Scopus. The review reveals multiple interconnected research streams spanning consumer behavior, sustainability transition, business model innovation, regulatory frameworks, and service design. Both bibliometric and thematic analyses are used to better understand the state of repair service literature. Synthesizing the extant research, this review confirms that the research domain has deep roots and has experienced unprecedented growth, characterized by evolving trends, contexts, and levels of theoretical and methodological rigor. In addition, this thesis categorizes and synthesizes the research themes of repair services literature into three categories, including micro (e.g., the attitude-behavior gap in repair adoption, barriers and enablers to repair utilization), meso (e.g., repair service business model design for repairability), and macro (e.g., right-to-repair legislation and circular economy integration), and shows the relationship among them. The developed frameworks, by combining literature streams, show that strengthening repair services requires micro-level, meso-level, and macro-level insights to meet evolving regulatory and circular-economy standards. This scoping review advances repair service research by delivering comprehensive domain mapping, synthesizing fragmented literature, and proposing a strategic research agenda and guidance for practitioners.
Keywords: repair services; scoping review; sustainability; consumer behavior; business models; right to repair; circular economy.